A Simulation-based Optimization Approached to Design a Proposed Warehouse Layout on Bicycle Industry - Sienera, Farrel Stefan; Octavia, Tanti; Winoto, Desi (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
The finished goods must be stored in a warehouse before the items are dispatched. Due to the increasing demand in 2020, there will be an increase in the quantity of items, which will cause the finished goods warehouse at PT X to reach capacity. This issue lengthens the flow through the warehouse and makes it easier for the items to sustain damage. To improve capacity, the firm is building a new finished goods warehouse, and it wants to organize the two warehouses so that the displacement time is as short as possible. This study utilized simulations to calculate the time and dedicated and class-based storage strategies to establish the layout. This study utilized simulations to determine the time and dedicated and class-based storage approaches to establish the layout. According to the findings, the dedicated storage technique has a total displacement distance of 703,952 meters and an average moving duration of 3.37 minutes per pallet. These findings are not as useful as the class-based storage technique, which has 705,961 meters and an average pallet turn time of 3.53 minutes.